Microvascularized Fibular Bone Grafting for the Treatment of Mandibular Expansive Osseous Dysplasia ‑ A Case Report - Barbeiro, Camila de Oliveira [UNESP]; Verzola, Mario Henrique Arruda; Barbeiro, Roberto Henrique [UNESP]; Tachibana, Wilson Tadao; León, Jorge Esquiche; Bufalino, Andreia [UNESP] (Wolters Kluwer, 2023)
Rationale: Osseous dysplasia (OD) is a benign fibro‑osseous lesion classified as periapical, focal or florid with some rare cases being diagnosed as expansive OD. Patient Concerns: A 43-year-old female presented with gross mandible expansion and tooth displacement. Diagnosis: Imaging scans revealed an expansive lesion in the anterior mandible, with varying opacity in the central region, and other smaller lesions in the region of teeth #37 and #47, consistent with expansive OD. Treatment: Surgical resection followed by immediate reconstruction of the mandibular defect using a microvascularized fibular graft. Outcomes: The patient had a 4-year follow-up, with adequate mandibular bone continuity, mastication, swallowing, and speaking ability reestablished. Take-away Lessons: Immediate reconstruction after large surgical resection is required as tissues retract over time, hampering late reconstructions. Microvascularized fibular graft aims at adequate and functional rehabilitation with osseointegrated implants and long‑term follow‑up is needed as florid OD may evolve into expansive OD.
Keywords: Bone dysplasias; case report; florid cemento‑osseous dysplasia; mandibular reconstruction; vascular grafting